The road to smart airports: Bibliometric analysis of digital transformation by using R language. - Şahin, İhsan Emrecan; Durmaz, Vildan (Work, 2024)
BACKGROUND: The accumulated knowledge has led to a state of misunderstanding about the precise meanings of digitalization, and a precise framework to define smart airports is still missing. OBJECTIVE: This study aims to reveal the current status and future direction of smart airports and digital transformation in the academic literature and to provide a comprehensive definition for smart airports. METHODS: The identified keywords were searched in the Web of Science database covering the years 1989-2024 and a total of 372 studies were found. These studies were then analyzed using Bibliometrix (R package). RESULTS: We determined that the most influential academic source on the themes is the Journal of Air Transport Management, and the collaboration index in the literature is three. While conferences are the most productive sources in this field, academic journals are mostly cited in studies. Academic studies typically employ and evaluate "performance" and "model," "impact" and "air," and "economic development" and "location" in tandem, despite the distinction between technological and managerial issues. CONCLUSION: In the light of the findings, the definition of a smart airport can be "an airport ecosystem where personalized service is provided to users by using Industry 4.0 technologies on the basis of big data analysis and real-time sharing between objects; digitalization is turned into a holistic organizational culture starting from top management to cover all personnel; the decision-making process is carried out autonomously within the entire airport operation network; and the main goal of competitive advantage and high-level user experience is provided uninterruptedly."